Topics in integrative neuroscience : from cells to cognition - Pomerantz, James R.; Cambridge eBooks (Cambridge : Cambridge University Press, 2008)
Neuroscience is progressing so rapidly that even expressions such as 'by leaps and bounds' fail to capture the pace of its growth. Questions that once were thought to be unanswerable - perhaps even unaskable - have been both asked and answered, and questions once unthinkable, are routine. Topics in Integrative Neuroscience has singled out four of the most important problems in neuroscience: higher order perception; language; memory systems; and sensory processes. The volume presents original contributions by many of the leading researchers in those fields, and with an initial chapter covering neuroethics. It is impossible to capture fully the sweep of discoveries that emerged from the 'Decade of the Brain' within the covers of a single volume. It is possible, however, to provide a sample, both in recognition of what has been accomplished and as a harbinger of what is surely to come.
Neuroscience, choice and responsibility / Patricia S. Churchland -- Attention as an organ system / Michael Posner and Jin Fan -- Cortical dynamics and visual perception / Charles Gilbert -- Cortical mechanisms of visuospatial attention in humans and monkeys / Sabine Kastner, Peter De Weerd, and Leslie Ungerleider -- Varying degrees of plasticity in different subsystems within language / Lisa D. Sanders, Christine M. Weber-Fox, Helen J. Neville -- The functional architecture of speech perception / David Poeppel and Martin Hackl -- Varieties of silence : the impact of neuro-degenerative diseases on language systems in the brain / Karalyn Patterson [and others] -- Why is language unique to humans? / Jacques Mehler, Marina Nespor, and Marcela Pena -- Memory systems / Larry R. Squire and Craig E.L. Stark -- A brain system for declarative memory / Seth J. Ramus and Howard B. Eichenbaum -- The role of the lateral nucleus of the amygdala in auditory fear conditioning / Hugh T. Blair [and others] -- On crucial roles of hippocampal NMDA receptors in acquisition and recall of associative memory / Kazu Nakazawa, Matthew A. Wilson, Susumu Tonegawa -- Song selectivity, singing, and synaptic plasticity in songbirds / Michele M. Solis [and others] -- Voltage-dependent sodium currents in hair cells of the inner ear / Julian R.A. Wooltorton [and others].
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Higher nervous activity; Perception; Language and languages; Memory; Electronic books